(untitled) (Journal of Rangpur Medical College, 2025)
Background: Epilepsy is one of the most prevalent and debilitating chronic neurological illnesses. Treatment adherence is one of the determinants of seizure control in persons with epilepsy (PWE). The purpose of this study was to assess adherence to antiepileptic drugs (AEDs) and factors associated with non-adherence in a sample of Bangladeshi PWE attended to an Epilepsy Clinic of a tertiary hospital in Bangladesh. Objective: The aim of study was to assess the extent of AED adherence and the factors influencing AED adherence among PWE. Methods: This analytic cross-sectional study was conducted in the Department of Neurology at Rangpur Medical College Hospital, Rangpur, Bangladesh, from July 2022 to June 2023. The patients were recruited from the epilepsy clinic. Data on adherence to medication and related factors for each patient were gathered using an interviewer administered structured questionnaire. Adherence was defined as not missing a dose and non-adherence is missing a dose or stopping treatment in the last month. Results: Of a total of 225 patients studied, 63(28%) patients were non-adherent with regards to AEDs. There were no demographic differences (based on gender, age, residential location, education, marital status, socioeconomic status, and seizure type) between adherent and non-adherent patients. The primary reason for non-adherence was forgetfulness or inability to buy drugs (66.6%), followed by a Lack of understanding of the need for long-term medication (22.2%). PWE who were on single AED were more likely to be adherent to AED than those were on polytherapy number of AEDs and adherence (p=0.037). Patients not-adherent to AEDs had a longer duration of illness [9.5 (4.0-17.0) years] (p<0.001). than the patient’s adherent to AEDs [median (Interquartile rage) 5.0 (2-11) years] Conclusions: About one-third of PWE needed to be more compliant with their medication. If the treatment of PWE is restricted to monotherapy as far as possible and they are educated about the duration of therapy and possible adverse effects of AEDs, non-adherence may be reduced. J Rang Med Col. March 2025; Vol.10, No.1:22-27